2006
DOI: 10.1017/s0022215106004373
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of first branchial cleft anomalies: the Sheffield experience

Abstract: Abnormalities of the first branchial cleft are rare. They may present with a cutaneous defect in the neck, parotid region, external auditory meatus or peri-auricular area, or with inflammatory or infective lesions at these sites. A retrospective case note review of the patients treated by the senior author is presented. This group consisted of 18 patients and represents the largest published UK series to date. Eleven patients (65 per cent) had undergone incomplete surgery prior to referral. Over half the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the current study, recurrence was found in seven patients (8.1%, 7/86) and two cases (2.3%, 2/86) with microtia suffered from EAC stenosis after surgery. Scar adhesions from previous infection or surgery as well as from acute inflammation made it difficult to completely remove lesions, causing the recurrence rate to increase to 20% 23,24 . Four out of seven patients who relapsed had a history of drainage or surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, recurrence was found in seven patients (8.1%, 7/86) and two cases (2.3%, 2/86) with microtia suffered from EAC stenosis after surgery. Scar adhesions from previous infection or surgery as well as from acute inflammation made it difficult to completely remove lesions, causing the recurrence rate to increase to 20% 23,24 . Four out of seven patients who relapsed had a history of drainage or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Scar adhesions from previous infection or surgery as well as from acute inflammation made it difficult to completely remove lesions, causing the recurrence rate to increase to 20%. 23,24 Four out of seven patients who relapsed had a history of drainage or surgery. Surgery was not recommended for FBCAs with acute inflammation and the complete dissection of suspicious lesions was performed in patients with a history of inadequate treatment or infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, choosing the optimal surgical time and surgical approach is very important. As reported, recurrence rates were as high as 20% when excision was performed in the acutely inflamed stage [ 24 ]. Repeated infection in the lesion might result in inflammatory adhesion in surrounding tissues and cause structures to be difficult to identify, which may increase the risk of recurrence and injury to the facial nerve.…”
Section: Discussionmentioning
confidence: 99%